Professional Development, Motivation, and Community in a Moscow In-service Recertification Course - Tony Hull (National Research University Higher School of Economics, 2015)
Between September 2010 and May 2013, the author conducted six cycles of an 8-week recertification course for in-service English teachers in Moscow, Russia. The course syllabus was built on developing a community of practice, as a motivating factor in teacher development. The community was fostered both during in-person meeting time and online participant interaction. While the participants' objectives were varied, the overarching goal of the course - beyond knowledge and skill building - was to engender a sense of ownership among the participants, both of the course itself and of their own continuing professional development. This was realized in both small incremental ways, such as launching a new discussion online, and in bolder, farther-reaching ways, such as organizing a mini-conference for a local school district.